EMG analysis during skiing of a para-alpine skier with the suspected somatoform disorder - Ishige, Y.; Inaba, Y.; Hakamada, N.; Yoshioka, S.; Kobayashi, A. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: In paralympic alpine skiing, "classification" is undertaken to group athletes into Sport Class which aim to ensure that the impact of impairment is minimized and sporting excellence determines which athlete is ultimately victorious (International Ski and Snowboard Federation, 2022). This time, we report on a supplemental examination for the skier who had discrepancies between the results of muscle strength testing and walking and skiing ability.